PROFESSIONAL COMMUNITY AS A SOCIAL MECHANISM OF REALIZATION OF PERSONNEL POLICY IN HEALTH CARE - O. V. Plotnikova (Исследования и практика в медицине, 2016)
The role of medical professional societies as a social mechanism of realization of personnel policy in the Russian health care system is characterized. The social nature of this mechanism is analyzed on the levels of Russian society, social groups, health workers and at the level of individual physician and health worker. According to the data of sociological survey of participants of X (XXVI) Emergency Pirogov Congress of doctors (may 2016), 93% of the doctors evaluating the state of Russian health care, pointed to the inherent manifestation of the crisis. This suggests that the Russian government, declaring himself at the same time by the customer, performer and supervisor of medical programs that inefficiently responds to the queries of patients as the ultimate consumers and the medical community. Under the theme of this study at the Congress were the main objectives of the professional medical community: licensing and certification of professional activity of doctors of all specialties; organization of advanced training of doctors; the control of activities of doctors; the creation and support of information databases on doctors; direct participation in policy income for the medical staff; the involvement of health personnel in policy development processes and health management.